Kualitas Pelayanan Puskesmas Terhadap Pasien Lanjut Usia Di Puskesmas Abeli Kecamatan Abeli Kota Kendari - Alghani, Fadillah; Utha, Arifin; Amir, Muh (REZ PUBLICA, 2021)
This study aims to determine the quality of public services on the satisfaction of elderly patients and the factors that affect the quality of service on the satisfaction of elderly patients at Abeli Public Health Center, Abeli District, Kendari City. The informants in this study were the Director of the Abeli Puskesmas, Abeli District, Kendari City, the Head of Public Relations at the Abeli Puskesmas, Abeli District, Kendari City, and 3 (three) people who received services at Abeli Puskesmas Abeli District, Kendari City. The results showed that the quality of public services at Abeli Public Health Center, Abeli District, Kendari City was seen from the dimensions of physical evidence with a poor category, reliability dimensions with good categories, responsiveness dimensions with good categories, assurance dimensions with good categories, and empathy dimensions with poor categories. Supporting factors that affect the quality of public services at Abeli Public Health Center, Abeli District, Kendari City are Leadership Factors, Team Work Spirit Factors, and Employee Job Satisfaction Factors. Inhibiting factors that affect the quality of public services at Abeli Public Health Center, Abeli District, Kendari City, namely there are still facilities that are not yet available and the presence of employees who are less friendly to service users.